Encyclopedia of nonlinear science - Scott, Alwyn, 1931- (Routledge, 2005)
Provides a useful overview of core mathematical background, and applications of nonlinear science to key problems in ecology and biological systems, chemical reaction-diffusion problems, geophysics, economics, etc.